Geguritan Aji Rama Rena Analisis Struktur dan Makna - Dwija Nandana Persada, Ida Bagus; Agung Mulyawati, Tjok. Istri; Puspawati, Luh Putu (Humanis; Vol 20 No 1 (2017), 2017)
Research on Geguritan Aji Rama Rena is about the analysis of structure and meaning. This analysis has a purpose to reveal the structure and meaning contained in the Geguritan Aji Rama Rena. This study uses structural theory and meaning. The methods and techniques used in this research are divided into three stages: (1) methods and techniques of data provision using repetitive reading method (heuristic) assisted by recording technique and translation techniques, (2) methods and techniques of data analysis using method Qualitative and analytic descriptive techniques, (3) methods and techniques of presentation of data analysis results using formal methods and informal methods assisted by deductive and inductive techniques. The result of this research is forma structure which consists of language and literature code, language variety and language style and content structure. Variety of language using the language of bali andap, madia, and ancient Javanese language. The style of the language consists of comparative language styles, contradictions, and linkage style. The content structure consists of the beginning, the middle, the end. Besides this research reveals the meaning of the meaning of the teachings of rwa bhineda, the meaning of the teaching of tri rna, the meaning of kharmaphala